Simulated gastric hydrolysis and developmental toxicity of dimethyltin bis(2-ethylhexylthioglycolate) in rats - Kirf, Dominik; Costlow, Richard; Nasshan, Hans; Frenkel, Peter; Mondimore, Donna (Frontiers in Toxicology, 2023)
Dimethyltin dichloride is used as the putative toxophore for dimethyltin bis-alkylthio esters in a read-across approach. Recent chemical and toxicological investigations challenges this read across as data on dioctyltin bis(2-ethylhexyl thioglycolate) and dibutyltin bis(2-ethylhexyl thioglycolate) showed the dialkyltin thioglycolates do not generate dialkyltin dichloride. Results obtained by 119Sn-NMR spectroscopy demonstrated that dimethyltin bis(2-ethylhexyl thioglycolate), the smallest commercially manufactured dialkyltin thioester molecule of this kind, hydrolyzed to dimethyltin chloro-(2-ethylhexyl) thioglycolate under simulated gastric conditions. These studies did not detect dimethyltin dichloride. Dimethyltin bis(2-ethylhexyl thioglycolate) was administered orally to timed-pregnant Wistar-Han rats in an Arachis oil vehicle at 5, 10, and 25 mg/kg/day [Gestation Day 6 (GD6) through GD20] with no maternal deaths observed. At 25 mg/kg/day treatment statistically significant reductions occurred in feed consumption (9%), maternal body weight (2.4%) and adjusted maternal weight gain (68%). There were no adverse gestational findings. Maternal thymus weight was significantly reduced in rats at 25 mg/kg in the absence of changes in hormone levels of T3, T4 or TSH. There were no effects on fetal growth, no dose-dependent pattern of external, visceral, or skeletal malformations and no increase in anatomical variations at any dose group. Based on the obtained experimental data it is concluded that dimethyltin bis(2-ethylhexyl thioglycolate) forms dimethyltin chloro-(2-ethylhexyl thioglycolate), not dimethyltin dichloride, in the stomach environment at pH 1.2, and dimethyltin bis(2-ethylhexyl thioglycolate) was not teratogenic nor fetotoxic in rats. The maternal NOAEL was 10 mg/kg/day, and the developmental NOAEL was 25 mg/kg/day, the high dose. The maternal LOAEL was 25 mg/kg/day based on decreased food consumption, lower adjusted mean body weight gain and reduced maternal thymus weight.